Preferential Placement of Aligned Nitrogen Vacancy Centers in Chemical Vapor Deposition Overgrown Diamond Microstructures. Issue 1 (5th October 2021) - Götze, Arne; Striegler, Nico; Marshall, Alastair; Neumann, Philipp; Giese, Christian; Quellmalz, Patricia; Knittel, Peter
Abstract : The usefulness of nitrogen vacancy (NV) centers in diamond is augmented by a low defect and impurity density in the surrounding host material, and applications benefit from the ability to control the position of the NV centers. Herein, a process to create NV centers on single‐crystalline diamond microstructures by chemical vapor deposition (CVD) is presented. Pyramidal structures with 111 side facets are formed during the intrinsic overgrowth of dry chemically etched cylindrical pillars on a substrate with 100 surface orientation. A thin nitrogen‐doped epitaxial layer is deposited on top of the pyramids resulting in the creation of NV centers exclusively on the 111 pyramid side faces. Optically detected magnetic resonance (ODMR) and spin echo measurements reveal preferential alignment of the NV centers in a single 111 direction and a T 2 time of 55 μs . The T 2 time of the NV centers is limited by the surrounding substitutional nitrogen (P1 center) concentration of [P 1 ] = 5 ppm . A low density of other paramagnetic spin noise is detected by double‐electron electron resonance (DEER) measurements. Abstract : Nitrogen vacancy (NV) centers are selectively placed on a diamond substrate with their crystallographic axes aligned to enhance fluorescence contrast. This is achieved by nitrogen‐doped chemical vapor deposition (CVD) overgrowth of dry chemically etched diamond structures. The resulting NV centers exhibit long spin coherence times and minimal residual spin noise is detected in the host diamond crystal.